فاعلية الذات المهنية لمستشاري التوجيه والارشاد المدرسي و المهني في العمل الارشادي التربوي بولاية الأغواط - عائشة عريشة; بشرى بن شريف; حسين بن بوداود (My University, 2023)
The study aimed to identify the Professional self of psychological counselors in the work of educational counseling in the state of Laghouat. the study was applied to a sample 49 guidance counselors in the state of Laghouat, They were selected through a random sample at the School and Vocationnel Guidance and Counseling, In our study we relied on thedescriptive approach that serves our study, to achieve the objectives of the study, we used the 51 items questionnaire distributed over 4 dimensions, and after statistical treatment through (SPSS) we reached the following results: - There are statistically significant differencesin the degrees of the school's professional personality, vocational guidance and counselors in providingeducationaladvice The processattributed to the gender variable .- There are statisticallysignificantdifferences in the degrees of selfprofessionalism of school and vocational guidance and counseling counselors in educational counseling due to the seniority variable. - There are statisticallysignificantdifferences in the degrees of selfprofessionalism of school and vocational guidance and counseling counselors in educational extension work due to the variable of specialization. Keywords: Professional psychology, psychologi calcoun sellors, educational counseling work..